PENDATAAN ALUMNI SECARA ONLINE UNTUK MENDAPATKAN DATA TRACER ALUMNI - Primaadi Airlangga; Mochamad Chumaidi; Fika Ridaul Maulayya (KH. A. Wahab Hasbullah University, 2016)
Tracer study is a mean to gather information of the alumni on regards to learn about their progress in career, their implementation of skills they learn in their study, and opinion about them from people who work alongside them. The importance of tracer study lies in the processing data from the alumni and producing information that can be used to increase the learning materials, learning methods, motivation of the current students, and quality of service given by the university. Collecting data from graduated University students is not an easy task. The major issue in the data gathering is the distance between the University and the data givers’ location because most of them are not grouped in areas near the campus which make them unable to directly submit the questionere to the faculty they studied. Other dificulties faced by the university which conduct tracer study are the alumni’s ocupation which prohibit them for going to University, time limit given for the alumni to submit their form, cost used for buying and printing papers, more over the form’s layout and content that consist of things that need to be skipped based on options the participant’s choice which make it confusing and dificult to gather valid data.The result of this research is an aplication that can handle the inputs of tracer study by the alumni and produce information about alumni’s progress from those inputs, especialy for those who had graduated from their alma mater for more than six months. Several improvement that can be achieved by this application caompared to the previous hand in form method are instant collecting as soon as the user press the submit button, automatic processing which can eliminate submision due date because the user can fill the form any time there is a change in their data, and automatic text and graphical reporting which can be seen anytime with real time update which can be used for producing data for decision making in the university where this application is used.Keyword : angket, alumni, UNWAHA, tracer study, online